Human pythiosis, Brazil - Bosco, Sandra de Moraes Gimenes [UNESP]; Bagagli, Eduardo [UNESP]; Araújo Jr., João Pessoa [UNESP]; Candeias, João Manuel Grisi [UNESP]; Franco, Marcello Fabiano de; Marques, Mariangela Esther Alencar [UNESP]; Mendoza, Leonel; Camargo, Rosangela Pires de [UNESP]; Marques, Silvio Alencar [UNESP] (Centers for Disease Control and Prevention (CDC), 2005)
Pythiosis, caused by Pythium insidiosum, occurs in humans and animals and is acquired from aquatic environments that harbor the emerging pathogen. Diagnosis is difficult because clinical and histopathologic features are not pathognomonic. We report the first human case of pythiosis from Brazil, diagnosed by using culture and rDNA sequencing.
Keywords: amphotericin B; itraconazole; potassium iodide; adult; Brazil; case report; clinical feature; DNA sequence; histopathology; hospital admission; human; male; nucleotide sequence; pythiosis; Pythium; skin disease; Humans; Infection; Male; Middle Aged